1996
DOI: 10.1161/01.res.78.2.188
|View full text |Cite
|
Sign up to set email alerts
|

SM22α, a Marker of Adult Smooth Muscle, Is Expressed in Multiple Myogenic Lineages During Embryogenesis

Abstract: SM22 alpha is a calponin-related protein that is expressed specifically in adult smooth muscle. To begin to define the mechanisms that regulate the establishment of the smooth muscle lineage, we analyzed the expression pattern of the SM22 alpha gene during mouse embryogenesis. In situ hybridization demonstrated that SM22 alpha transcripts were first expressed in vascular smooth muscle cells at about embryonic day (E) 9.5 and thereafter continued to be expressed in all smooth muscle cells into adulthood. In con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
293
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(309 citation statements)
references
References 45 publications
14
293
0
2
Order By: Relevance
“…For example, SM ␣-actin and SM22␣ are expressed as early as E9.5 in the cells surrounding the dorsal aorta, 28 whereas myocardin is not detectable in this tissue until E12.5. 11 Because myocardin transcript is detected in the primitive heart at E9.5, 11 initial induction of these early SMC markers may not require myocardin.…”
Section: Discussionmentioning
confidence: 99%
“…For example, SM ␣-actin and SM22␣ are expressed as early as E9.5 in the cells surrounding the dorsal aorta, 28 whereas myocardin is not detectable in this tissue until E12.5. 11 Because myocardin transcript is detected in the primitive heart at E9.5, 11 initial induction of these early SMC markers may not require myocardin.…”
Section: Discussionmentioning
confidence: 99%
“…In transgenic mice the 441-bp SM22␣ promoter is active in arterial but not visceral SMCs (29,31). Therefore, the demonstration that the lacZ reporter gene encoded by AdSM22-lacZ was expressed in visceral as well as vascular SMCs was somewhat surprising.…”
Section: Discussionmentioning
confidence: 99%
“…SM22 ␣ is an early marker of the SMC lineage that is expressed at high levels exclusively in visceral and vascular SMCs during postnatal development (28)(29)(30). We have shown that the 441-bp SM22 ␣ promoter activates transcription exclusively in arterial SMCs during postnatal development in transgenic mice (31).…”
Section: Introductionmentioning
confidence: 87%
“…However, there is a possibility of contamination by adventitial and interstitial fibroblasts. To rule out this potential confound, we stained isolated cells for SM22α, α-smooth muscle actin (α-SMA), both VSMC markers 7,8 , and vimentin, a fibroblast marker 9 , at passages 1-2 ( Figure 2). We observed no change of these markers through passage 2.…”
Section: Representative Resultsmentioning
confidence: 99%